Distribution of Zakat fi Sabilillah for the Tahfiz Program at the Baitul Mal Board in Aceh in the Perception of Ulama Dayah - Burhanuddin Abd. Gani; Zaiyad Zubaidi (Sharia and Law Faculty, 2022)
Fi sabilillah in the Fiqh conception, its meaning is interpreted as people fighting in defense of religion. For this meaning, Ulama (Islamic scholars) clung to distributing zakat fi sabilillah to the mustahiq as guided by the meaning of the text contained in the fiqh books. But in practice, Baitul Mal in Aceh distributes zakat fi sabilillah for the tahfiz Qur'an program. Therefore, based on the issue’s description, it is necessary to conduct a more comprehensive study to determine the legal basis of Baitul Mal in Aceh for channeling zakat fi sabilillah for the Tahfiz Qur'an Program, how the program is realized, and how Ulama Dayah perceive the practice. This research employed qualitative methods in the form of field studies using a conceptual approach. Based on the results of the study, it was found that Baitul Mal in Aceh in giving zakat fi sabilillah for the Tahfiz Qur'an Program already refers to the provisions in the Qur'an and also other rules stipulated in the provisions of the Qanun Baitul Mal, which was then the program realized through the distribution of scholarships to students in the form of a tahfiz program. In addressing this issue, Ulama Dayah do not deny the distribution of zakat fi sabilillah for the tahfiz Qur’an program, although conceptually the interpretation of the meaning of zakat fi sabilillah can only be given to those who fight in defense of religion. Their view is based on the existence of the values of benefit contained in Baitul Mal’s practice.Fi sabilillah dalam konsepsi fikih, ditafsirkan maknanya dengan orang berperang membela agama. Atas makna inilah kemudian para ulama berpegang dalam menyalurkan zakat fi sabilillah kepada para mustahiq sebagaimana petunjuk dari makna teks yang tertera dalam kitab-kitab fikih. Namun praktiknya, Baitul Mal di Aceh menyalurkan zakat fi sabilillah untuk program tahfiz al-Qur`an. Maka atas dasar deskripsi permasalah tersebut perlu adanya kajian lebih komprehensif sehingga diketahui apa dasar hukum Baitul Mal di Aceh menyalurkan zakat fi sabilillah untuk Program Tahfiz al-Qur`an, bagaimana realisasi programnya dan bagaimana persepsi ulama dayah terhadap praktik tersebut. Penelitian ini menggunakan metode kualitatif dalam bentuk kajian lapangan dengan menggunakan pendekatan konseptual. Berdasarkan hasil penelitian ditemukan bahwa Baitul Mal di Aceh dalammenyalurkan zakat fi sabilillah untuk Program Tahfiz al-Qur`an sudah mengacu pada ketentuan yang ada baik dalam al-Qur`an dan juga aturan lain yang diatur dalam ketentuan Qanun Baitul Mal yang kemudian programnya direalisasikan melalui penyaluran beasiswa kepada santri dalam bentuk program tahfiz. Para ulama dayah, dalam menyikapi persoalan ini tidak menolak penyaluran zakat fi sabilillah untuk program tahfiz al-Qur`an, meskipun secara konsep penafsiran makna fi sabilillah hanya dapat diberikan kepada orang yang berperang membela agama. Pandangan mereka ini didasarkan pada adanya nilai-nilai kemaslahatan yang terkandung dalam praktek Baitul Mal tersebut.